Pengaruh Social Media Marketing dan Content Marketing Terhadap Minat Beli: Studi Kasus pada Followers Instagram MBD Kontraktor - Muhammad Teguh Syahvira Nasution; Syafrizal Helmi Situmorang; Beby Karina Fawzeea Sembiring (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The rapid development of digital technology has influenced marketing strategies, including the use of social media marketing (SMM) and content marketing (CM) to enhance consumer buying interest. This study aims to analyze the impact of SMM and CM on the buying interest of Instagram followers of MBD Kontraktor. Using a descriptive quantitative method, the study involved 208 active Instagram followers. Data were collected through online questionnaires, documentation studies, and direct observation. The results show that SMM has a positive and significant impact on buying interest. This is evident from active interaction strategies, relevant information, and creative content delivered through social media. CM also significantly influences buying interest, characterized by relevant, informative, easily understood, and consistent content. Both strategies, when combined, exhibit a stronger positive impact, confirming that the synergy of SMM and CM effectively attracts consumer interest. This study contributes to the academic literature on digital marketing and offers practical guidance for companies to improve their marketing strategies. Based on these findings, companies are expected to better understand the importance of utilizing social media and high-quality content to enhance consumer appeal and loyalty.